Husband's Unemployment and Wife's Labor Supply – The Added Worker Effect across Europe - Julia Bredtmann; Sebastian Otten; Christian Rulff (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
This paper investigates the responsiveness of women's labor supply to their husband's loss of employment - the so-called added worker effect. While previous empirical literature on this topic mainly concentrates on a single country, we take an explicit internationally comparative perspective and analyze whether the added worker effect varies across the European countries. In doing so, we use longitudinal data from the European Union Statistics on Income and Living Conditions (EU-SILC) covering the period 2004 to 2011. For our pooled sample of 28 European countries, we find evidence for the existence of an added worker effect, both at the extensive and at the intensive margin of labor supply. Women whose husbands become unemployed have a higher probability of entering the labor market and changing from part-time to full-time employment than women whose husbands remain employed. However, our results further reveal that the added worker effect varies over both the business cycle and the different welfare regimes within Europe. – – Dieser Artikel beschäftigt sich mit der Anpassung des Arbeitsangebots von Frauen in Reaktion auf den Jobverlust ihres Partners, dem sog. 'Added Worker Effect'. Während sich die bisherige Literatur überwiegend auf Studien für spezifische Länder konzentriert hat, nehmen wir bewusst eine international vergleichende Perspektive ein und untersuchen, inwiefern der Added Worker Effect über die verschiedenen Wohlfahrtsstaatssysteme in Europa variiert. Unsere empirischen Analysen basieren auf Längsschnittdaten der 'European Union Statistics on Income and Living Conditions (EU-SILC)' für den Zeitraum 2004 bis 2011. Für unseren aus 28 europäischen Ländern bestehenden Datensatz finden wir Evidenz für das Vorliegen eines Added Worker Effects: Frauen, deren Partner im vergangenen Jahr arbeitslos wurde, haben eine höhere Wahrscheinlichkeit, in den Arbeitsmarkt einzutreten sowie den Umfang ihrer Arbeitszeit zu erhöhen, gegeben dass sie schon am Arbeitsmarkt partizipieren. Darüber hinaus finden wir jedoch eine hohe Variation in der Existenz und der Stärke des Added Worker Effects sowohl über den Verlauf des Konjunkturzyklus als auch über die verschiedenen Wohlfahrtsstaatssysteme in Europa.
Keywords: J22; J64; J82; 330; added worker effect; labor supply; unemployment; cross-country analysis